MANAGEMENT OF IMPROVEMENT OF LOCAL POULTRY CULTIVATION - Aisyah Lubis; Iwan Hasrizart (Jurnal Ekonomi, 2023)
The purpose of this study was to determine the feasibility analysis of local chicken farming by giving a promol 12. The experimental method provides a treatment of the research object and then examines how the consequences of the treatment given. Descriptive analysis takes the problem or focuses attention on the problem as it is. The parameters observed were production costs, income, profit and loss analysis and r/c rasio analysis. Local chickensmaintenanceis a fairly efficient business based on a total r/c ratio of 1.13, P0 treatment is a more efficient business category with an arc/c ratio of 1.16 and higher than treatment using promol 12, and is feasible to develop. Local chicken smaintenancebusiness with promol 12 is not recommended because it does not provide a decent income marked by a low r/c ratio (P1 1.01, P2 1.05, P3 1.13) while P0 (1.16).